2017
DOI: 10.1055/s-0042-124501
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Reproducibility of Two-Dimensional Wall Motion Tracking (WMT) in Fetal Echocardiography

Abstract: Objective The primary objective of this study was to determine the feasibility and reproducibility of 2-dimensional speckle tracking imaging based on the wall motion tracking (WMT) technique in fetal echocardiography. The secondary objective was to compare left and right ventricular global and segmental longitudinal peak strain values. Methods A prospective cross-sectional study was performed. Global and segmental longitudinal peak strain values of the left ventricle (LV) and right ventricle (RV) were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 70 publications
3
32
0
Order By: Relevance
“…The authors showed that already >30 fpc resulted in excellent strain accuracies for longitudinal and circumferential strain. 35 Further, the authors concluded that in contrast to previous publications on tissue Doppler imaging (TDI)-derived strain and strain rate, higher frame rates, for example, of >100 Hz, seem not to be needed for peak longitudinal circumferential or radial 2D strains. 34 This is in line with the results of our recent study on the feasibility and reproducibility of 2D WMT in fetal echocardiography.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The authors showed that already >30 fpc resulted in excellent strain accuracies for longitudinal and circumferential strain. 35 Further, the authors concluded that in contrast to previous publications on tissue Doppler imaging (TDI)-derived strain and strain rate, higher frame rates, for example, of >100 Hz, seem not to be needed for peak longitudinal circumferential or radial 2D strains. 34 This is in line with the results of our recent study on the feasibility and reproducibility of 2D WMT in fetal echocardiography.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, we could achieve global and segmental LPSS values with high intra-and inter-observer correlations. 35 Further, the authors concluded that in contrast to previous publications on tissue Doppler imaging (TDI)-derived strain and strain rate, higher frame rates, for example, of >100 Hz, seem not to be needed for peak longitudinal circumferential or radial 2D strains. Especially in the field of TDI for proper acquisition of tissue velocities and the short duration of myocardial tissue movements, high frame rates are required in order to obtain an adequate temporal resolution.…”
Section: Discussionmentioning
confidence: 70%
“…4,[6][7][8][9][10][11][12] The frame rate (FR) used to acquire ultrasound images is the primary determinant of temporal resolution and remains one of the most important considerations of the reliability of 2D STEderived myocardial deformation imaging; the degree of reliability appears to be influenced by the acquisition rate. [14][15][16][17][18][19][20] We have previously demonstrated feasibility and reproducibility with archived Digital Imaging and Communications in Medicine (DICOM) data with 30 and 60 frames per second (fps), 21,22 while others have been working with the original FR frequency ranging between 44 and 150 fps. [14][15][16][17][18][19][20] We have previously demonstrated feasibility and reproducibility with archived Digital Imaging and Communications in Medicine (DICOM) data with 30 and 60 frames per second (fps), 21,22 while others have been working with the original FR frequency ranging between 44 and 150 fps.…”
Section: Recent Evaluation Of Deformation Values By Two-dimensional Stementioning
confidence: 99%
“…13 Currently there is a wide variation in the suggested FR utilized for STE-derived strain measurements in the fetus. [14][15][16][17][18][19][20] We have previously demonstrated feasibility and reproducibility with archived Digital Imaging and Communications in Medicine (DICOM) data with 30 and 60 frames per second (fps), 21,22 while others have been working with the original FR frequency ranging between 44 and 150 fps. [23][24][25][26][27] Reproducibility has also been shown to be most robust when cine loops are obtained with a specific FR-to-heart rate (HR) ratio.…”
Section: Recent Evaluation Of Deformation Values By Two-dimensional Stementioning
confidence: 99%
See 1 more Smart Citation